Demonstration Method as an Effort to Improve Fiqh Learning Outcomes for MI Al Aziz Probolinggo Students - Muhammad, Devy Habibi; Nurlaila Maulidiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This journal discusses efforts to improve the academic achievement of third-grade students at MI Al-Aziz, located in the Kanigaran District of Probolinggo Regency. The research focuses on the implementation of the demonstration method in the Fiqih subject for third-grade students at MI Al-Aziz and its impact on students' learning achievement. The attention is directed towards the low academic achievement of students, which has not yet reached the minimum passing grade of 75. The Classroom Action Research (CAR) method is employed as an approach to address this issue. The research results indicate an improvement in students' learning achievement when the demonstration method is applied from Cycle 1 to Cycle 2. In Cycle 1, approximately 64.71% of students achieved proficiency, while in Cycle 2, this figure increased to around 82.35%. These findings affirm that the demonstration method is effective in enhancing students' learning achievement. Therefore, based on the results of this research, it is recommended that teachers adopt the demonstration method in teaching, making adjustments according to the appropriate material for application with the demonstration method.